Co-creating creative self-efficacy to build creative performance and innovation capability for business success: a meta-analysis - Yodchai, Natthawut; Ly, Pham Thi Minh; Tran, Lobel Trong Thuy (Creativity Studies, 2022)
Although creativity is considered a key driver of successful business, few studies examine it in a form of creative mindset. By means of a meta-analysis of 58 studies (n = 22,427), this study explores how creative mindsets and creative self-efficacy engage in affecting creative performance and innovation capability that result in business success. The results suggested that a growth mindset is positively related to creative self-efficacy, which can influence creative performance and innovation capability while a fixed mindset has negative effects. More importantly, creative performance contributes more to business success than innovation capability does. Thus, these results established the role of creative mindsets in enhancing business success. Therefore, this study provides scholars and practitioners the necessary evidence for making statistical inferences on creativity-based model and enhancing the business success.